2012
DOI: 10.1002/zaac.201200419
|View full text |Cite
|
Sign up to set email alerts
|

The Protonation of Acetamide and Thioacetamide in Super­acidic Solutions: Crystal Structures of [H3CC(OH)NH2]+AsF6 and [H3CC(SH)NH2]+AsF6

Abstract: Acetamide and thioacetamide react with the superacid solutions HF/MF 5 (M = As, Sb) under formation of the corresponding salts [H 3 CC(OH)NH 2 ] + MF 6 and [H 3 CC(SH)NH 2 ] + MF 6 -(M = As, Sb), respectively. The reaction of DF/AsF 5 with acetamide and thioacetamide lead to the corresponding deuterated salts [H 3 CC(OD)ND 2 ] + AsF 6 and [H 3 CC(SD)ND 2 ] + AsF 6 -, respectively . The salts are characterized by vibrational and NMR spectroscopy, and in the case of [H 3 CC(OH)NH 2 ] + AsF 6 and [H 3 CC(SH)NH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Therefore the calculated frequencies as well as Raman and IR intensities of [CH 3 SO 2 N X 3 ] + · 3HF ( X = D, H), which were carried out in the harmonic approximation and taken into account for the vibrational assignments. In previous studies the method of adding HF molecules to the naked cation already became apparent as a powerful tool for the simulation of hydrogen bonds in the solid state , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore the calculated frequencies as well as Raman and IR intensities of [CH 3 SO 2 N X 3 ] + · 3HF ( X = D, H), which were carried out in the harmonic approximation and taken into account for the vibrational assignments. In previous studies the method of adding HF molecules to the naked cation already became apparent as a powerful tool for the simulation of hydrogen bonds in the solid state , …”
Section: Resultsmentioning
confidence: 99%
“…[1] However, more systematic studies that eventually led to development of 'superacid chemistry' were performed much later (in the 60s and 70s) by Olah and Hogeveen who studied non-aqueous systems (such as SbF 5 /HF and HSO 3 F/SbF 5 ) [2][3][4][5][6][7] and by Gillespie who formulated the first definition of a 'superacid' as any acid stronger than 100 % sulfuric acid (i. e., having its Hammett acidity function H 0 smaller than À 12). [8,9] Due to their unusual properties, superacids are the subject of ongoing theoretical [10][11][12][13][14] and experimental [15][16][17][18][19][20][21][22][23][24] investigations focused mainly on their structure, acidity, and stability. Our contribution to these studies include predicting the acidity of the aluminumbased Al n F 3n /HF (n = 1-4) systems [25] and the compounds containing In, Sn and Sb, [26] Au, [27] Ti and Ge, [28] investigating the saturation of the acidity of nHF/AlF 3 and nHF/GeF 4 (n = 1-6) superacids caused by increasing the number of surrounding HF molecules, [29] describing the fragmentation process of the HAlF 4 and HGaF 4 superacids induced by an excess electron attachment, [30,31] and demonstrating the catalytic usefulness of various superacids.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely strong acidic compounds such as binary Lewis–Brønsted superacids have been the subject of extensive theoretical and experimental investigations since 1927 . It should be pointed out, however, that superacid chemistry was mainly developed in the second half of the 20th century. Among the numerous superacidic systems described thus far, fluoroantimonic acid (HF/SbF 5 or HSbF 6 ) deserves special attention because of its astonishing properties (the HSbF 6 superacid is 10 16 times stronger than 100% sulfuric acid). In addition, fluoroantimonic acid is commonly considered the strongest liquid superacid known, despite the fact that even stronger superacids might exist (according to theoretical predictions) in the gas phase. , Because of their unique properties, mixed Lewis–Brønsted superacids play the role of the catalyst in various chemical reactions such as hydrogenation processes, and they can easily protonate a number of organic compounds (including very weak bases). It is notable that the superacids most frequently used in laboratories, HF/SbF 5 and HF/AsF 5 , are usually prepared using an excess of hydrogen fluoride with respect to the Lewis acid , (increasing the number of Brønsted acid molecules surrounding the Lewis acid causes the enhancement of the acidity of a given system), whereas the excess of SbF 5 or AsF 5 with respect to HF results in the formation of dinuclear (Sb 2 F 11 ) − or (As 2 F 11 ) − anions, which are commonly known as superhalogen anions. The presence of various superhalogen anions [e.g., (SbF 6 ) − , (Sb 2 F 11 ) − , (AsF 6 ) − , and (As 2 F 11 ) − ] in superacidic solutions was also proven by earlier experimental studies. Recently, it was shown that superhalogens can be treated as natural precursors of the Lewis–Brønsted superacids, and thus, the search for novel strong acidic systems should be performed among their daughter anions combined with the additional proton. …”
Section: Introductionmentioning
confidence: 99%